In the shadow of politicisation - Krapels, GEAM (2011)
This thesis researches the variation in levels of liberalisation within the European services market, focusing in detail on four selected service sectors (i.e. postal services, electricity services, healthcare services and the services covered by the Services Directive) from 2001 until 2011. In this thesis, I propose a model of European integration capable of explaining the exact levels of liberalisation in each service sector. I argue that the level of liberalisation can be explained by looking at the drivers of integration (i.e. expected economic benefits from further integration and the level of supranational activity), which determine the societal demand for further integration and the shape legislators’ preferences and constraints, and the intervening influence of adhoc politicisation (i.e. the influence of public opinion through mass mobilisation). To illustrate this, this thesis applies a two-tiered approach of analysis. First, it explains the context in which the legislation is made to understand the economic implications of the proposed legislation, the level of supranational activity preceding the tabling of the legislation and the preferences of all actors involved. Second, taking preferences as exogenously given, this thesis applies a method of process tracing to study in detail the negotiations between legislators – the amending stage of the legislation. The case studies show that the drivers are crucial to explain the general demand for integration and at the same time show how politicisation, taking various guises, influences the level of liberalisation – primarily by altering legislators’ relative power. Particularly interesting is that politicisation can affect the negotiations even in absence of politicisation actually materialising causing some legislation to be made in the ‘shadow of politicisation’. These findings confirm existing explanations of European integration and add new insights as to how we can understand the process of European integration more generally.